NATURAL REGENERATION’S STUDY OF ARBOREAL SPECIES IN MATA DAS GALINHAS FRAGMENT, HUMID FOREST IN CATENDE’S CITY, PERNAMBUCO’S SOUTH ZONE - Silva, Wegliane Campelo da (2007)
The study was developed in the fragment situated in the Catende’s – PE city (Mata das Galinhas – 8º69'06" S; 35º69'08" W), in mesoregion of the pernambucana forest, more necessarily in the humid forest’s microregion, at 142 km of the capital. The area’s vegetacion is Humid Forest. The relief varies wavy to very wavy, with 199 m altitude. The soil is classified as red latisols dystrophic and red nitosols associated to latisols. The present work aims to study and evaluated the total natural regeneration of arboreal species in the forest fragment and to verify the diversity and structure of the species in the same one. For estimate the natural regeneration, were made systematically 16 subunits (samples with 5 x 5 m). These subunits were inserted in the middle samples (10 x 25 m) before used to evaluate the community arboreal phytossociology, with 50 meters between the ones. The regeneration study (CAP < 15 cm) was developed with heights divided in three categories (1 – individuals with minimum heights 1 < 2 m; 2 - individuals with minimum heights 2 < 3 m; 3 - individuals with heights > 3 m). Besides, the samply sufficient and diversity were calculated. In fragment was observed 31 botanical families and 60 arboreal species inside 194 individuals. 42 had been identified in level of species, 4 in sort level, 2 in family level and 2 are not identify. Ten species obtained bigest values for total natural regeneration of the samples population (RNT) and contribute with 53,78% of the total percentage, how is descript following way: Brosimum discolor Schott (9,98%), Protium heptaphyllum (Aubl.) Marchand (9,19%), Eschweilera ovata (Cambess.) Miers (8,01%), Thyrsodium spruceanum Benth. (7,0%), Dialium guianense (Aubl.) Sandwith (5,44%), Erythroxylum squamatum Sw. (3,32%), Cupania revoluta Rolfe (3,16%), Sorocea hilarii Gaudich. (2,66%), Cordia nodosa Lam. (2,52%) e Tapirira guianensis Aubl. (2,50%). These species had presented a good capacity of regeneration, probably they will be main responsible for the maintenance of forest’s structure and physiognomy. The diversity (H ') was 3,65 nats/ind for the fragment.